Evaluation of Foot Deformities in Patients With Ingrown Nails - Sarı, Nihal; Saylam Kurtipek, Gülcan; Ünal, Mehmet; Öztürk, Mehmet; Sarı, İlker Fatih (Dermatology Practical & Conceptual, 2024)
Introduction: Ingrown nail is a condition caused by the perforation of the periungual soft tissues on nail folds by the sides of nail plaque, causing inflammation and severe pain. Recently, the role of foot anatomical disorders in ingrown nail development has been emphasized.Objectives: The main objective of this study aimed to determine whether foot deformities played significant roles in ingrown nail development with objective radiological parameters.Methods: The study included 64 patients diagnosed with clinical ingrown nail and 71 patients as controls without any ingrown nail history. In both groups, we evaluated the bilateral foot radiographs of patients with ingrown nails for hallux valgus angle (HVA), interphalangeal angle (IPA), and intermetatarsal angle (IMA) associated with hallux valgus, and the calcaneal pitch angle (CPA), talohorizontal angle (THA), and talometatarsal angle (TMA) related to pes planus.Results: No significant difference was found in terms of hallux valgus radiological measurements of HVA, IPA and IMA as well as pes planus radiological measurements of CPA and TMA values, when compared to controls. THA was statistically significantly higher in the control group (P = 0.025). There was a moderate strength positive relationship between ingrown nail stage and measured TMA for pes planus diagnosis (rho = 0.326; P = 0.04), yet there are no significant correlations between ingrown nail stage and other angles.Conclusions: Therefore, we do not recommend foot anatomy correction in the prevention and treatment of ingrown nails, unless there is an accompanying foot deformity; however, pes planus is a foot deformity that can accompany patients with severely ingrown nails.